Worldwide Wisdom of the Crowd in Education and Development - Mishra, Sanjaya (REVISTA PARAGUAYA DE EDUCACIÓN A DISTANCIA (REPED), 2020)
The paper outlines the global challenges faced and particularly highlights the challenges in education, which has the potential to impact the achievement of all the 17 Sustainable Development Goals (SDGs), if planned and designed well. Using the framework of the wisdom of crowd and crowdsourcing, the paper presents two educational innovations that have the potential to change the educational landscape. Open educational re-sources (OER) and massive open online courses (MOOCs) use the power of the web to provide access to quality education and lower the cost making education affordable to all. It makes a case for rethinking education and development through the prism of harnessing the power of the masses to offer 21st Century learning beyond the four walls of educational institutions.